Identifying Best Practices for a Successful Study Abroad Program - Mary T. Rodriguez; T. Grady Roberts (Journal of International Agricultural and Extension Education, 2011)
The purpose of this study was to identify the best practices of study abroad programs before, during, and after the experience. The results of this study will add further to implementing quality educational programs in agricultural and life sciences. A qualitative methodology with participant observation was employed to provide a thick and rich examination of a study abroad experience conducted in Latin America. Results provided specific best practices for activities before, during, and after such an experience. Recommendations and implications are provided.
Keywords: Study abroad; globalization; educational programs; international experience